The Prosperous Justice Party of Bandung City and its Mix Strategy Marketing in the 2019 Election - Muhammad Taufiq; Mudiyati Rahmatunnisa; Ferry Kurnia Rizkiyansyah (Universitas Medan Area, 2020)
General Election (Pemilihan Umum/Umum) is an arena for political parties to fight for seats in parliament through various political campaign strategies they carry out. The success of the Prosperous Justice Party (PKS) Bandung City in obtaining the majority of 13 seats in the 2019 Election is an interesting political case to study. This study aims to describe and analyze the political marketing strategies that the legislative candidates from the Prosperous Justice Party (PKS) of Bandung City carry out. Using the marketing mix theory, this study looks at 4 dimensions, namely Product, Place, Price, and Promotion. A descriptive-qualitative approach is applied. This study conducts interviews with representatives of the former PKS candidates who were the members of the parliament of Bandung City in the period of 2019-2024. This study indicates that PKS candidates for the City of Bandung Parliament have succeeded in implementing a marketing mix strategy. They employ it effectively and efficiently and reach a wider and more inclusive segment. They also apply campaign narratives that are close to voter’s needs through direct marketing strategies.